2018
DOI: 10.21037/jtd.2018.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Excessive periostin expression and Th2 response in patients with nasal polyps: association with asthma

Abstract: Background: Periostin has been shown to be upregulated in chronic rhinosinusitis with nasal polyps (CRSwNP), especially in the CRSwNP patients with asthma. However, the underlying mechanism that how periostin contributes to the polyp genesis remains unclear.Methods: In this study, we collected 63 CRSwNP patients' nasal polyps (NPs) and 25 control subjects' uncinated tissues. The expressions of periostin, thymic stromal lymphopoietin (TSLP), and other proinflammatory cytokines were examined using IHC staining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 37 publications
(44 reference statements)
1
37
1
Order By: Relevance
“…Among the symptoms, rhinorrhea best correlated with periostin levels (R=0.36; p=0.02). This result is consistent with the available literature in that an increased expression of periostin correlates with an increased activity of the glands of the respiratory tract and an increased volume of their secretion [ 33 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the symptoms, rhinorrhea best correlated with periostin levels (R=0.36; p=0.02). This result is consistent with the available literature in that an increased expression of periostin correlates with an increased activity of the glands of the respiratory tract and an increased volume of their secretion [ 33 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in children with NM hypertrophy in the medial surface of the conchae, there was significantly more periostin, i.e., 21.6 [10.7; 1516.8] ng/mg; p=0.02. This, however, contradicts the literature data about an increased expression of the gene encoding for periostin and an increase in periostin-protein in sinonasal polyps and systemic bio-substrates [ 30 , 45 , 46 ]. For example, in a study by Asano et al [ 48 ], serum periostin levels in patients with asthma with chronic rhinosinusitis and nasal polyps were significantly higher (130.0±46.6 ng/ml) than in patients without nasal polyps (87.9±37.7 ng/ml); p=0.001.…”
Section: Discussioncontrasting
confidence: 60%
“…Wei et al . found that tissue periostin had a significant positive relationship with previous ESS and asthma in 63 CRSwNP patients [ 12 ]. Unlike the literature, our study detected no significant relationship between serum and tissue periostin and asthma in the CRSwNP group ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative CT can be used for surgical planning, as well as for follow-up and postoperative treatment [ 10 ]. Moreover, some studies positively correlate periostin with the severity of CRSwNP in radiological evaluations [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periostin promotes adhesion and migration of epithelial cells and is associated with CRSwNP (Ishida et al, 2012;Ohta et al, 2014;Laury et al, 2015;Milonski et al, 2015;Shiono et al, 2015;Wang et al, 2015;Ebenezer et al, 2017;Xu et al, 2017;Wei et al, 2018;Yang et al, 2018;Lehmann et al, 2019) and asthma (Carpagnano et al, 2018;Wei et al, 2018). The EMT process is driven by an array of factors such as WNT, reactive oxygen species, proteases, HIF1, IL-13 Epiregulin, Oncostatin M, and IL-1 (Oyer et al, 2013;Batzakakis et al, 2014;Schleimer, 2017;Aazami et al, 2018;Yang et al, 2018;Tomaszewska et al, 2019).…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 99%